KESEIMBANGAN ANTARA AKSI-REAKSI GAYA LUAR BANGUNAN SEBAGAI KERAMAHAN TERHADAP ALAM SEMESTA: Diskursus - Rita Laksmitasari Rahayu (Universitas Indraprasta PGRI, 2021)
Modernism has its origins in classical Greece. Almost all processes of modernity are anthropocentric, human-centered processes. Modernity has not stopped to this day, although there are post moderns. Humanism is undergoing a renewal from a mere natural human view of man, not just a natural being but also a supernatural, immanent creature. Humans are seen not only as faber mundi but more as imago dei; the image of God. Philosophy moves from theocentric to anthropocentric nature with value and history at each stage of its transformation. Anthropocentric has become a fundamental understanding of humans today. In fact, this universe will respond to all things humans do that are creative. There is no possibility or concern over data religion or dataism. The human element in this research is still needed. Research work is not in the form of nominal numbers, but more on a humanistic approach. Science is not arrogant, does not feel strong and is unable to walk without human assistance. Science can accept the universe as a partner in work.